Drastic reduction of thermal conductivity in hexagonal AX (A = Ga, In & Tl, X = S, Se & Te) monolayers due to alternative atomic configuration. (October 2021) - Majumdar, Arnab; Chowdhury, Suman; Ahuja, Rajeev
Abstract: Several two-dimensional chalcogenide materials have been in the limelight in the recent past for their promising thermoelectric properties. It is well established that the thermoelectric performance of materials improves on reducing the physical dimensionality of the system. Two-dimensional hexagonal chalcogen (S, Se and Te) bearing compounds of Ga, In and Tl have already been studied extensively in literature. But in those phases, the group-13 non-chalcogen atoms occupy the two inner planes while the chalcogens occupy the two outer planes of the unit cell. In this work, we have proposed the alternate arrangement in which the chalcogen atoms occupy the two inner planes while the group-13 atoms occupy the two outer planes of the unit cell. Unprecedentedly, this alternate arrangement shows much lower thermal conductivity that leads to superior thermoelectric performance. In this work we have studied in details the thermoelectric properties of hexagonal AX (A = Ga, In & Tl, X = S, Se & Te) monolayers and compare the results having both the atomic arrangements. The very low lattice thermal conductivity of this new arrangement is due to the outermost valence s-orbital lone pair of the chalcogens which leads to enhanced anharmonicity. We have explained these results from the anti-crossing of the phonon branches as well. The electronic, dynamical, thermodynamical and elastic properties have also been studied. We think that these results should have significant impact on the synthesis of high-performance thermoelectric materials based on chalcogenides of gallium, indium and thallium. Graphical Abstract: ga1 Highlights: The position of the group 13 and chalcogen atoms in AX (A = Ga, In & Tl, X = S, Se & Te) have been flipped. Ab initio calculations of thermal conductivity, electronic properties and mechanical properties have been determined. The new configuration yields dynamically stable structures too with much lower elastic constants and Debye temperatures. The high anharmonic scattering and weak bonds lead to ultralow thermal conductivity due to the lattice vibrations. The ultralow thermal conductivity lead to extremely high values of thermoelectric figure of merit.